METODE PENGUATAN WARGA DALAM MELAKUKAN MITIGASI PADA MASA PANDEMI COVID-19 DI KABUPATEN MUNA BARAT - Yamin Yamin; Ruslin Ruslin; Rina Andriyani; Syahabudin Syahabudin; La Aba (Universitas Halu Oleo, 2021)
Corona virus disease (COVID-19) is an infectious disease caused by the recently discovered corona virus. Common signs and symptoms of COVID-19 infection include acute respiratory symptoms such as fever, cough and shortness of breath. The average incubation period is 5-6 days with the longest incubation period of 14 days. Severe cases of COVID-19 can cause pneumonia, acute respiratory syndrome, kidney failure and even death. The purpose of this activity is to provide strengthening of Community Strengthening in Mitigation against the COVID-19 Outbreak in West Muna Regency. The implementation of activities is carried out by providing outreach to the community through both online and offline. Online activities are carried out by communicating through the WhatsApp application while suspiciously by socializing with direct meetings or distributing leaflets with the material of the Healthy Living Community Movement (GERMAS), Clean and Healthy Lifestyle (PHBS), Movement Using Masks (GEMAS), Family Medicinal Plants (TOGA) ) and the use of disinfectants and antiseptics.——————————————————————————————————————Penyakit virus corona (COVID-19) adalah penyakit menular yang disebabkan oleh virus corona yang baru-baru ini ditemukan. Tanda dan gejala umum infeksi COVID-19 antara lain gejala gangguan pernapasan akut seperti demam, batuk dan sesak napas. Masa inkubasi rata-rata 5-6 hari dengan masa inkubasi terpanjang 14 hari. Pada kasus COVID-19 yang berat dapat menyebabkan pneumonia, sindrom pernapasan akut, gagal ginjal, dan bahkan kematian. Tujuan kegiatan ini adalah untuk memberikan penguatan Penguatan Masyarakat dalam Mitigasi Menghadapi Wabah COVID-19 di Kabupaten Muna Barat. Pelaksanaan kegiatan dilakukan dengan memberikan penyuluhan kepada masyarakat melalui baik daring maupun luring. Kegiatan daring dilakukan dengan komunikasi melalui aplikasi whattsApp sedangkan secara lurig dengan sosialisasi dengan pertemuan langsung maupun penyebaran leaflet dengan materi Gerakan Masyarakat Hidup Sehat (GERMAS), Pola Hidup Bersih dan Sehat (PHBS), Gerakan Menggunakan Masker (GEMAS), Tanaman Obat Keluarga (TOGA) dan Penggunaan disinfektas dan Antiseptik.